Preparation and Performance Characterization of Warm-Mix Rejuvenated Bioasphalt. (13th August 2020) - Zhang, Zhu; Li, Jiusu; Duan, Zhenjun; Zhang, Shuaipeng; Lou, Menglei
Abstract : Reclaimed asphalt pavement (RAP) material is generally under a large amount of aged asphalt coated on the surface of the aggregates, which often limits its (RAP) wide application. Bioasphalt is a renewable material with constituent components that are comparable to regular petroleum asphalt and has the potential to rejuvenate the performance of the aged asphalt in RAP materials. In this laboratory study, the optimum bioasphalt dosage for rejuvenating and optimizing warm-mix rejuvenated bioasphalt (WBA) performance, in the presence of styrene-butadiene-styrene (SBS) and naphthenic oil additives, was investigated. The laboratory test results of the single-factor and orthogonal experiment indicated that the optimal dosage of bioasphalt in WBA was 30% at 4% SBS and 10% naphthenic oil, respectively. The test results further indicated that the WBA's ductility properties were highly responsive to the bioasphalt dosage. Naphthenic oil, on the other hand, had the greatest impact on the WBA fluidity. Likewise, the Brookfield viscosity experimentation showed that the fluidity of WBA and aged asphalt with different contents at 30%, 40%, 50%, 60%, and 70%, respectively, satisfactorily met the Chinese construction requirements. The adhesion test indicated excellent adhesion and good moisture stability properties for WBA. The resultant PG grades of WBA blended with 40% and 70% aged asphalt were PG 64-34 and PG 70-22, respectively. Microstructure and surface morphology analysis showed carbonyl absorption peaks with high rejuvenation and surface-crack repair potential for the WBA over the control asphalt that was evaluated in the study.